2015
DOI: 10.1007/s12282-015-0597-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative diagnosis of sentinel lymph node (SLN) metastasis using 3D CT lymphography (CTLG)

Abstract: CTLG can select the candidate with truly node negative cases in early breast cancer patients, because it predicts lymph node metastasis preoperatively from natural status of the lymphographic image. It also might omit the SLN biopsy itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
28
0
2
Order By: Relevance
“…The same region of interest was drawn and copied for the measurements of each lymph node in all subsequent series. Mean, minimum and maximum HU values were recorded. Enhancement pattern of the lymphatic vessels (not assessable vs. stagnant, dilated, or detoured lymph vessel) . For better identification of the pathways of the lymphatic vessels, additional multiplanar and maximum intensity projection reformatted images were created.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same region of interest was drawn and copied for the measurements of each lymph node in all subsequent series. Mean, minimum and maximum HU values were recorded. Enhancement pattern of the lymphatic vessels (not assessable vs. stagnant, dilated, or detoured lymph vessel) . For better identification of the pathways of the lymphatic vessels, additional multiplanar and maximum intensity projection reformatted images were created.…”
Section: Methodsmentioning
confidence: 99%
“…Enhancement pattern of the lymphatic vessels (not assessable vs. stagnant, dilated, or detoured lymph vessel) . For better identification of the pathways of the lymphatic vessels, additional multiplanar and maximum intensity projection reformatted images were created.…”
Section: Methodsmentioning
confidence: 99%
“…Takahashi et al [7] used CT-LG to identify SLNs of 218 breast cancer patients. Nakagawa et al [19] used CT-LG to detect SLN metastases of the breast in 228 patients. Suga et al [20] identified breast SLNs using MRI-LG in volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel nodes that are not stained or poorly stained (<50%) suggest presence of metastasis [34]. Other criteria used by some authors are partial staining of sentinel nodes (stain defect, mottled or ‘crab claw' stain), stagnant or dilated lymph vessels, and detoured lymph vessels [35]. The sentinel nodes are marked on the skin using a laserlight navigator system.…”
Section: Non-operative Axillary Stagingmentioning
confidence: 99%
“…The sentinel node detection rate for CTLG preoperatively ranges from 98 to 100% and for CTLG-assisted sentinel node biopsy is 100% [34,35,36]. However, CTLG alone has an unacceptably high false-negative and false-positive rate for macrometastases (17.9 and 16.4%, respectively) [34].…”
Section: Non-operative Axillary Stagingmentioning
confidence: 99%